Evaluating Cybersecurity Threats of the Increasing of using Gadget by the Children in Indonesia: An Analysis and Protection Strategies - Tambunan, Marcella D; Siagian, Candra Tandi Reinhard; yusdartono, Habib Muharry (Bahasa Indonesia, 2024)
The use of digital gadgets in daily life has been ingrained in the lives of children, even toddlers, as information and communication technology progresses. This age group faces serious hazards associated to cyber vulnerability even while simple access to technology presents chances for learning and cognitive growth.Thus, this study is doing to collect the report about all threads already happens in Indonesia. The strategy classified into three approach: person (parents who have responsibility for the children), technology security (digital product itself), and regulation addressed to a more effective mitigation strategies in addressing cyber vulnerability among the children of Indonesia.